2019
DOI: 10.1002/er.4835
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performances of earth air heat exchangers through Constructal design

Abstract: Summary Earth to air heat exchanger (EAHE) is a well‐known technique used to preheat or precool outdoor air before blowing it into a building. However, its geometry is often very simple as it consists in one or multiple straight pipes, while more complex arrangements can be found in heat exchangers design. In this paper, we explore the advantage of designing an EAHE as a network through the Constructal law point of view. A methodology is first proposed to design a single pipe EAHE when the need is defined in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies developed in recent years have shown high thermal potential for EAHE installations (Vaz, 2011;Vaz et al 2011Vaz et al , 2014, also estimated by models developed in Brum (2013); Brum et al (2012Brum et al ( , 2013. Aims of recent study have included analyzing its construction parameters (Brum et al, 2016); and improving its performance utilizing numerous pipes (Rodrigues et al, 2015;Brum, 2016;Brum et al, 2017Brum et al, , 2019b; Brum, Labat and Lorente (2019a). Work carried out by Estrada et al (2018) presents the efficiency of EAHEs in several regions of Brazil, demonstrating that tropical climates are also a good option for installing EAHEs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies developed in recent years have shown high thermal potential for EAHE installations (Vaz, 2011;Vaz et al 2011Vaz et al , 2014, also estimated by models developed in Brum (2013); Brum et al (2012Brum et al ( , 2013. Aims of recent study have included analyzing its construction parameters (Brum et al, 2016); and improving its performance utilizing numerous pipes (Rodrigues et al, 2015;Brum, 2016;Brum et al, 2017Brum et al, , 2019b; Brum, Labat and Lorente (2019a). Work carried out by Estrada et al (2018) presents the efficiency of EAHEs in several regions of Brazil, demonstrating that tropical climates are also a good option for installing EAHEs.…”
Section: Introductionmentioning
confidence: 99%